Validate or falsify: Lessons learned from a microscopy method claimed to be useful for detecting Borrelia and Babesia organisms in human blood. Issue 6 (2nd June 2016) - Aase, Audun; Hajdusek, Ondrej; Øines, Øivind; Quarsten, Hanne; Wilhelmsson, Peter; Herstad, Tove K.; Kjelland, Vivian; Sima, Radek; Jalovecka, Marie; Lindgren, Per-Eric; Aaberge, Ingeborg S.
Abstract: Background A modified microscopy protocol (the LM-method) was used to demonstrate what was interpreted as Borrelia spirochetes and later also Babesia sp., in peripheral blood from patients. The method gained much publicity, but was not validated prior to publication, which became the purpose of this study using appropriate scientific methodology, including a control group.Methods Blood from 21 patients previously interpreted as positive for Borrelia and/or Babesia infection by the LM-method and 41 healthy controls without known history of tick bite were collected, blinded and analysed for these pathogens by microscopy in two laboratories by the LM-method and conventional method, respectively, by PCR methods in five laboratories and by serology in one laboratory.Results Microscopy by the LM-method identified structures claimed to be Borrelia - and/or Babesia in 66% of the blood samples of the patient group and in 85% in the healthy control group. Microscopy by the conventional method for Babesia only did not identify Babesia in any samples. PCR analysis detected Borrelia DNA in one sample of the patient group and in eight samples of the control group; whereas Babesia DNA was not detected in any of the blood samples using molecular methods.Conclusions The structures interpreted as Borrelia and Babesia by the LM-method could not be verified by PCR. The method was, thus, falsified. This study underlines the importance of doing proper test validation before new or modified assays are introduced.